PENDEKATAN PSIKOLOGI UNTUK KEPUTUSAN INVESTASI DI MASA PANDEMI COVID-19 - Asri Nur Wahyuni; Rudi Suryo Kristanto (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
The investment world is one of the areas that has felt the impact, this is due to various restrictions on activities which ultimately affect the activities of the national economy. It is important for investors to maintain, follow and be able to analyze pandemic Covid-19 conditions with proper observations and calculations so that total losses can be minimized as small as possible. A psychological approach to investment decision-making can be done with many factors. The level of trust, historical data, social relationships, emotions, and past experiences can be one of the bases for making investment decisions. The data in this study are primary data obtained by distributing questionnaires to the public in Indonesia via a google form. The sample taken in this study was 100 respondents. Multiple linear regression analysis has been used to analyze the data in this study. Heuristics, Emotion, and considering the past variables have an effect on investment decisions. However, overconfidence and social interaction variables have no significant effect on decision-making when investing.